Diagnosis of apical hypertrophic cardiomyopathy: T-wave inversion and relative but not absolute apical left ventricular hypertrophy. (15th March 2015) - Flett, Andrew S.; Maestrini, Viviana; Milliken, Don; Fontana, Mariana; Treibel, Thomas A.; Harb, Rami; Sado, Daniel M.; Quarta, Giovanni; Herrey, Anna; Sneddon, James; Elliott, Perry; McKenna, William; et al.
Abstract: Background: Diagnosis of apical HCM utilizes conventional wall thickness criteria. The normal left ventricular wall thins towards the apex such that normal values are lower in the apical versus the basal segments. The impact of this on the diagnosis of apical hypertrophic cardiomyopathy has not been evaluated. Methods: We performed a retrospective review of 2662 consecutive CMR referrals, of which 75 patients were identified in whom there was abnormal T-wave inversion on ECG and a clinical suspicion of hypertrophic cardiomyopathy. These were retrospectively analyzed for imaging features consistent with cardiomyopathy, specifically: relative apical hypertrophy, left atrial dilatation, scar, apical cavity obliteration or apical aneurysm. For comparison, the same evaluation was performed in 60 healthy volunteers and 50 hypertensive patients. Results: Of the 75 patients, 48 met conventional HCM diagnostic criteria and went on to act as another comparator group. Twenty-seven did not meet criteria for HCM and of these 5 had no relative apical hypertrophy and were not analyzed further. The remaining 22 patients had relative apical thickening with an apical:basal wall thickness ratio > 1 and a higher prevalence of features consistent with a cardiomyopathy than in the control groups with 54% having 2 or more of the 4 features. No individual in the healthy volunteer group had more than one feature and no hypertension patient had more than 2. Conclusion: A cohort of individuals exist with T wave inversion, relative apical hypertrophy and additional imaging features of HCM suggesting an apical HCM phenotype not captured by existing diagnostic criteria. Highlights: The normal left ventricular myocardium tapers towards the apex. There exists an apical HCM variant with relative rather than absolute apical hypertrophy. T-wave inversion and relative apical hypertrophy are core features. Additional features include a dilated left atrium, scarring, apical cavity obliteration and apical microaneurysms.